Evaluation of strategic building maintenance and refurbishment budgeting method Schroeder - Christen, Markus; Schroeder, Jules; Wallbaum, Holger (International Journal of Strategic Property Management, 2012)
The method Schroeder is accepted amongst real estate professionals in Switzerland as a near standard for condition monitoring, budgeting of maintenance and refurbishment, and strategic decision support in point of building portfolios. It is based on the devaluation curves of 12 or more building elements. Main results are the actual and the prognosticated future building condition in percentage of its reinstatement value, the residual useful service life of building elements, and the calculation of future maintenance and refurbishment costs. 25 years after its first publication, this paper analyses the assumptions made, compares the method to other methods in this field, and validates the method in several steps, based on scientific or empirical evidence. Furthermore, a desktop simulation of a well-documented portfolio was performed and compared, the answers from a questionnaire amongst users are provided, and the partially controversial conclusions are discussed. First Publish Online: 8 Dec 2014